2019
DOI: 10.1136/vr.105003
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of corneal impression cytology in dogs and its application in the diagnosis of keratoconjunctivitis sicca

Abstract: ObjectiveDetermine morphological and morphometric parameters of corneal epithelium in dogs, and determine the cellular alterations that occur in canine keratoconjunctivitis sicca (KCS) using impression cytology.Study animals60 dogs divided into two groups: dogs with Schirmer tear test (STT) at least 15 mm/minute and absence of ocular disease, and dogs with STT less than 15 mm/minute and clinical signs of KCS.ProceduresImpression cytology was used to collect corneal samples. The percentage of eyes with cell cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…The agreement between the two evaluators in our study on these sample parameters was better in the affected eyes group than in the healthy eyes group. This difference could be explained by the presence of healthy cells in larger clusters or sheets [10] compared to the high proportion of individual inflammatory cells in the affected eyes. Cytology textbooks and materials available online contain few pictures of normal cells and mostly focus on the pathologies that can be observed.…”
Section: Discussionmentioning
confidence: 97%
“…The agreement between the two evaluators in our study on these sample parameters was better in the affected eyes group than in the healthy eyes group. This difference could be explained by the presence of healthy cells in larger clusters or sheets [10] compared to the high proportion of individual inflammatory cells in the affected eyes. Cytology textbooks and materials available online contain few pictures of normal cells and mostly focus on the pathologies that can be observed.…”
Section: Discussionmentioning
confidence: 97%
“…Morphological changes were found to be more frequent in dogs with lower STT values, and it was observed that the number of altered cells increased in proportion to a decrease in STT value. A significant difference was also observed in the number of pyknotic nuclei, with the number being higher in dogs with all stages of KCS than in healthy dogs 13 …”
mentioning
confidence: 87%
“…A signiicant diference was also observed in the number of pyknotic nuclei, with the number being higher in dogs with all stages of KCS than in healthy dogs. 13 Lejarza-Illaro and colleagues' results demonstrate that corneal impression cytology may be a useful additional diagnostic procedure that can be used to conirm a diagnosis of KCS. It may also have the potential to diferentiate between mild, moderate and severe cases of KCS.…”
Section: Dj Haeussler Jrmentioning
confidence: 97%
See 2 more Smart Citations